2011
DOI: 10.1002/humu.21442
|View full text |Cite
|
Sign up to set email alerts
|

Germline gain-of-function mutations of ALK disrupt central nervous system development

Abstract: Neuroblastoma (NB) is a frequent embryonal tumor of sympathetic ganglia and adrenals with extremely variable outcome. Recently, somatic amplification and gainof-function mutations of the anaplastic lymphoma receptor tyrosine kinase (ALK) gene, either somatic or germline, were identified in a significant proportion of NB cases. Here we report a novel syndromic presentation associating congenital NB with severe encephalopathy and abnormal shape of the brainstem on brain MRI in two unrelated sporadic cases harbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…This again illustrates that mutations that most strongly activate the tyrosine kinase domain might not be observed in patients without severe malformative phenotype. 29 Altogether, our results show that germline ALK mutations are rarely involved in sporadic neuroblastomas. Thus, systematic screening may not be proposed in non-familial cases.…”
Section: Discussionsupporting
confidence: 51%
“…This again illustrates that mutations that most strongly activate the tyrosine kinase domain might not be observed in patients without severe malformative phenotype. 29 Altogether, our results show that germline ALK mutations are rarely involved in sporadic neuroblastomas. Thus, systematic screening may not be proposed in non-familial cases.…”
Section: Discussionsupporting
confidence: 51%
“…The ALK gene, located at 2p23, encodes a receptor tyrosine kinase (RTK) that belongs to the insulin-receptor superfamily (4,5). Activating ALK mutations, mainly affecting residues located within the kinase domain, have been identified in sporadic, familial, and syndromic cases of NB (6)(7)(8)(9)(10)(11) and ALK amplifications have also been reported in a subset of sporadic cases (2,12). Furthermore, it has been suggested that the wild-type (WT) ALK receptor may exert oncogenic activity in NB when a critical threshold of expression is achieved (13).…”
Section: Introductionmentioning
confidence: 99%
“…The syndromic patients with de novo germline activating ALK mutations presented with an enlarged medulla obloganta evidenced by magnetic resonance imaging [9]. We therefore sought to document Alk expression in the brainstem and determine whether KI Alk F1178L mice exhibited abnormalities of this structure.…”
Section: Resultsmentioning
confidence: 99%
“…The observation of missing germline mutations relative to the somatic repertoire suggested that a highest activity of these mutated forms may induce severe effects during embryonic development resulting in embryonal lethality. Yet, a syndromic presentation associating congenital neuroblastoma with severe encephalopathy and abnormal shape of the brainstem has now been described in two sporadic cases harbouring de novo germline F1174V and F1245V ALK mutations [9]. These patients presented with major feeding difficulties, associated with poor sucking and swallowing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation